Implementasi Community Based Tourism dalam Pengembangan Objek Wisata Janti Park di Kabupaten Klaten - Putri, Na'ilah Cahaya; Gustaman, Fulia Aji (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
Janti Park is a village-owned tourist attraction managed by BUMDes, which includes local community participation. BUMDes Jaya Janti continues to make various development efforts to maintain the existence of the Janti Park tourist attraction so that it can continue to provide benefits to the community. The purpose of this research is to find out how BUMDes implements the concept of community-based tourism in an effort to develop Janti Park tourist attractions in Klaten Regency. This research uses qualitative research methods with data collection techniques in the form of observation, interviews, and documentation. The results showed that the implementation of the community-based tourism concept through community empowerment and community participation was able to develop tourist destination attributes at the Janti Park tourist attraction, namely attractions, amenities, accessibilities, and ancillary.